2012
DOI: 10.4166/kjg.2012.59.5.366
|View full text |Cite
|
Sign up to set email alerts
|

A Ten-year Follow-up of a Case with Gastric Adenoma Accompanied with Gastritis Cystica Profunda Treated by Endoscopic Submucosal Dissection

Abstract: Gastritis cystica profunda (GCP) is an uncommon hyperplastic benign lesion, and histologically characterized by hyperplasia and cystic dilatation of the gastric glands extending into the submucosal layer. GCP usually occurs at a gastroenterostomy site, although it can occasionally be found in an unoperated stomach. GCP is thought to be a possible precancerous lesion, since a few early gastric cancers associated with it were reported. Herein, we report a case of gastric adenoma associated with GCP in an unopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[ 7 ] Okada et al reported a negative stance towards surgical excision. [ 8 ] However, in certain cases, such as those with the possibility of malignant transformation during endoscopic surveillance, [ 9 ] cases leading to compromised quality of life due to gastrointestinal symptoms such as abdominal pain and nausea, and cases resistant to conservative treatment, surgical resection should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Okada et al reported a negative stance towards surgical excision. [ 8 ] However, in certain cases, such as those with the possibility of malignant transformation during endoscopic surveillance, [ 9 ] cases leading to compromised quality of life due to gastrointestinal symptoms such as abdominal pain and nausea, and cases resistant to conservative treatment, surgical resection should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…To date, two cases of recurrence have been reported after surgical resection (33,39). Meanwhile, a 10-year follow-up of a case of GCP in an unoperated patient revealed low-grade dysplasia, and the sizes of both the GCP and the adenoma overlying had increased during the follow-up period (45).…”
Section: Discussionmentioning
confidence: 99%
“…Its malignant potential should be valued because GCP accompanied by gastric adenocarcinoma has been documented in several reports [2,3,5-8]. Ten-year follow-up of a case with GCP in an unoperated patient revealed low-grade dysplasia, and the sizes of both the GCP and the adenoma overlying it increased during the follow-up period [14]. …”
Section: Discussionmentioning
confidence: 99%